Вибір параметрів вантажопідйомних крокуючих модулів при розробці технології монтажу великорозмірних покриттів - Черненко, К. В. (Ways to Improve Construction Efficiency, 2013)
Offered basic provisions perfection of technology of large-block construction single-storey buildings and structures and the choice of the basic parameters of load modules walking now focus on implementation This improvement mounting technology associated with large-block covers mechanization of operations and finding new - more effective organizational and technological solutions rearing, subject to mandatory installation process of concentration in the node "Headroom column which is increasing - the design of coatings, which were grown."